Arnold Lobel in indirect translation: The case of Frog and Toad in Croatian - Andraka, Marija; Milković, Ivana (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
It seems that, for various reasons, indirect translation still occupies a marginal role in Translation Studies (see Pięta 2014) and it has not asserted itself as a research field in its own right. This paper discusses the role of indirect translation and mediating languages in translating children’s literature. The reasons for indirect translations in the Croatian context are explained. The process of indirect translation is investigated within the theoretical background of retranslation. Indirect translation is exemplified by Arnold Lobel’s story The Surprise (from Frog and Toad All Year), a story which has been translated into Croatian through the medium of German. The reasons for indirect translation are investigated as well as the effects of indirect translation on the final translated text. The article examines signals of foreignisation and domestication in the target text and the extent to which they can be attributed to German as the mediating language and German culture as the mediating culture.